Analisis Perbandingan Model Prediksi Kebangkrutan Altman Z-Score, Springate, Grover, dan Zmijewski pada Perusahaan E-Commerce di Indonesia - Widi Nugroho; Kadar Nurjaman; Eva Novita Pratiwi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to evaluate the relevance of traditional bankruptcy prediction models in the context of digital companies, specifically within Indonesia's e-commerce sector. Although the e-commerce sector has experienced rapid growth, many companies in this sector continue to record sustained losses, raising questions about the accuracy of conventional bankruptcy models in assessing the financial condition of digital firms. This research employs a quantitative approach by analyzing the financial statements of three e-commerce companies listed on the Indonesia Stock Exchange: PT Bukalapak.com Tbk, PT Global Digital Niaga Tbk, and PT GoTo Gojek Tokopedia Tbk, covering the period from 2021 to 2024. The analysis utilizes four bankruptcy prediction models—Altman Z-Score, Springate, Grover, and Zmijewski—and includes the Kruskal–Wallis test to examine differences in outcomes among the models. The results indicate variations in predictions across models, suggesting differences in sensitivity when evaluating the financial condition of e-commerce companies. Furthermore, most models tend to classify these companies as being in financial distress, even though, operationally, they are still in a growth phase. These findings highlight the limitations of traditional bankruptcy prediction models in interpreting the financial characteristics of digital firms. The study implies that the application of bankruptcy prediction models should consider industry context, particularly for technology-based companies with growth patterns and financial structures that differ from those of conventional firms.